Dynamic changes of protein lactylation and their correlations with the glycolytic process during the postmortem acidification of broiler breast - Zhenxin Wang; Tong Xing; Lin Zhang; Liang Zhao; Feng Gao (Poultry Science)
ABSTRACT: This experiment aimed to reveal the dynamic changes of protein post-translational lactylation modifications and their correlations with the glycolytic process in broiler breast muscle within 48 h of postmortem acidification. The experiment involved 12 male AA broilers, 42 days old, with similar body weights (2.8 ± 0.05 kg). The breast fillets (Pectoralis major) were collected after slaughter, and samples were taken at various time points: 0, 15 min, 30 min, 45 min, 60 min, 2 h, 4 h, 6 h, 8 h, 12 h, 18 h, 24 h, 36 h, and 48 h postmortem. The results showed that the rate of glycogen decline in the muscle was highest at 45 min postmortem, and glycogen levels tended to stabilize at 8 h postmortem. The lactate content in the breast reached its highest level at 4 h postmortem and began to decrease, stabilizing at 24 h postmortem. Additionally, the glycolytic potential increased gradually in the first 4 h postmortem, decreased rapidly from 4 to 8 h. Similarly, lactylation modification levels were highest at 8 h postmortem, but stabilized at 12 h postmortem. During this process, the protein expression of the enzymatic lactylation modifier p300 showed no significant difference, while the content of the nonenzymatic lactylation substrate lactoylglutathione significantly decreased at 8 h and 24 h postmortem. Correlation analysis found that lactylation levels were negatively correlated with glycogen content, glucose content, glycolytic potential, and pH value, while positively correlated with lactate content. Besides, there was a positive correlation between lactylation levels and the protein expression of hexokinase, phosphoglycerate kinase 2, phosphoglucomutase 1, and triosephosphate isomerase. Additionally, lactylation levels were positively correlated with the activities of lactate dehydrogenase and phosphofructokinase. In summary, our experiment elucidated the dynamic changes in the entire glycolytic pathway in broiler pectoral muscle during acidification. During this process, lactylation modifications may participate in the glycolysis process by regulating the protein expression and activity of glycolytic enzymes.